Generasi Z : Perencanaan Keuangan dan Tingkat Stres - Farha; Baiq Rabiatul Adawiyah Kartika Wulan; Septia Ningsih; Sami'un (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the differences in stress levels between Generation Z individuals who engage in financial planning and those who do not Method: The research method employed is a quantitative approach using the Independent Samples t-test as the data analysis technique. Finding: The results show a significance value of 0.991 > 0.05, indicating that there is no statistically significant difference in stress levels between Generation Z individuals who practice financial planning and those who do not. These findings suggest that financial planning has not yet become a factor that significantly influences the stress levels of Generation Z. Novelty: This study contributes to the literature on financial literacy by examining how important financial planning impacts the stress levels of generation z.